Geographical patterns of incendiary and accidental fires in Springfield, Massachusetts, 1980–1984 - Bennett, William D. (Journal of quantitative criminology, 1987)
Arson is a serious crime occurring with increasing frequency in urban America today. To date, this crime remains poorly documented and seldom discussed in the literature, particularly from a geographical viewpoint. This study examined the spatial distribution and underlying factors associated with 440 arson and 732 accidental fires recorded in Springfield, Massachusetts, between 1980 and 1984. Based upon a series of dot and choropleth maps, there was evidence that both incendiary and accidental fires were clustered not only in specific Springfield neighborhoods but also along individual city streets. In an attempt to understand better the varying frequency of arson fires among the 36 census tracts in the Springfield study area, a multiple regression analysis was performed using census data reflecting a variety of social, economic, and housing characteristics. Two variables, representing housing vacancy and tenement-type housing, entered into the final regression equation. Together, these two variables accounted for 70.4% of the reported arson cases. A subsequent inspection of the regression residuals revealed a random geographical pattern, thereby precluding any simple explanation for the remaining unexplained arson. Other factors such as insurance, building ownership, and length of occupancy were thought to warrant examination in future research.